Highly wearable SSVEP-based BCI: Performance comparison of augmented reality solutions for the flickering stimuli rendering. (December 2021) - Arpaia, Pasquale; De Benedetto, Egidio; De Paolis, Lucio; D'Errico, Giovanni; Donato, Nicola; Duraccio, Luigi
Abstract: A highly-wearable single-channel Brain- Computer Interface (BCI) based on Steady-State Visually Evoked Potentials (SSVEPs) and Augmented Really (AR) is proposed. The SSVEP elicitation is provided by three AR head-mounted displays (HMD), namely Epson Moverio BT-350, Oculus Rift S, and Microsoft HoloLens. Four flickering stimuli, ranging from 8 Hz to 15 Hz, are used. The goal of the work is to carry out a performance comparison of the three aforementioned devices, in terms of stimuli visualization and SSVEPs detection. To this aim, classification accuracy and time response were assessed involving nine healthy volunteers during the experimental activity. The obtained results demonstrate that choosing an adequate HMD to render the flickering stimuli is decisive for obtaining adequate performances.